2015
DOI: 10.1007/s00266-015-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenesis of Human Adipose-Derived Stem Cells by In Vivo Co-graft with Auricular Chondrocytes from Microtia

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Co-culture and co-implantation of MSCs with AuCs has also been demonstrated with animal cells [ 23 , 25 ] and human-animal cell hybrids [ 21 , 22 ]. Only one previous co-implantation study combined both AuCs and stem cells of human origin, co-implanting AuCs with adipose-derived stem cells [ 24 ]. Similar to previous co-implantation studies, we observed comparable auricular cartilage generation between monocellular AuC and combined cellular implanted discs, while we also demonstrated that co-implantation of human cells can be extended to a full-scale ear construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-culture and co-implantation of MSCs with AuCs has also been demonstrated with animal cells [ 23 , 25 ] and human-animal cell hybrids [ 21 , 22 ]. Only one previous co-implantation study combined both AuCs and stem cells of human origin, co-implanting AuCs with adipose-derived stem cells [ 24 ]. Similar to previous co-implantation studies, we observed comparable auricular cartilage generation between monocellular AuC and combined cellular implanted discs, while we also demonstrated that co-implantation of human cells can be extended to a full-scale ear construct.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the behavior of AuCs in combination with MSCs. The co-implantation of AuCs with MSCs [ 21 23 ] or adipose-derived stem cells [ 24 ] has generated cartilage in vivo , yet the impact of these studies is limited due to the use of non-human cells [ 21 23 , 25 ], a lack of markers specific to elastic cartilage [ 21 , 22 ], or the absence of mechanical evaluation [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are a promising alternative cell source for cartilage repair. When appropriately stimulated, MSCs can differentiate into a variety of cell types, including cartilage-producing chondrocytes [ 4 , 15 19 ]. MSCs are frequently isolated from bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, common strategies to differentiate adult stem cells into chondrocytes still require the use of costly growth factors in the culture medium, such as transforming growth factor betas (TGF- β s), insulin-like growth factors, and bone morphogenetic proteins (BMPs). Of note, these additives could potentially lead to unexpected side effects during use in clinical practice [ 15 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level expression of Elastin was suggested that the production of elastin protein requires a longer period of cultures. Previous studies also reported that the bone marrow stem required 28 day of induction to express the high expression gene of Elastin (Cai et al 2015;Zhang et al 2015).…”
Section: Effect Of Tgf-βs On the Expression Of Chondrogenic Gene In Hmentioning
confidence: 90%